Efikasi Dry Ice terhadap Sitophilus oryzae dan Tribolium castaneum pada Beras Kemasan Plastik di Dataran Tinggi - Aisyah Aisyah; Subagiya Subagiya; Ato Sulistyo (Universitas Sebelas Maret, 2016)
Sitophilus oryzae and Tribolium castaneum are pest that can always attack rice in long periode storage. Rice in the plastic packaging that spread in market has not did fumigation, so the pest can attack faster than rice in sack packaging. This research was aimed to understand the effectiveness of dry ice to attack S. oryzae and T. castaneum with effect of dry ice to rice in plastic packaging at high land. This research used completely randomized design (CRD) with two factors. The first factor was dose of dry ice and second factor was wrapper of dry ice. The data was analyzed in variance analysis then continue with Duncan Mean Range Test (DMRT). The result showed that dose of dry ice 10 g/rice 5 kg can effect for 90,83 % mortality of S. oryzae and T. castaneum but it have not made effect for imago and larvae population. Also, dry ice was not make effect for rice weight and rice quality (color of rice, scent of rice and taste of rice).